2014
DOI: 10.1021/jp505908j
|View full text |Cite
|
Sign up to set email alerts
|

207Pb and119Sn Solid-State NMR and Relativistic Density Functional Theory Studies of the Historic Pigment Lead–Tin Yellow Type I and Its Reactivity in Oil Paintings

Abstract: Lead soaps (lead carboxylates) have been detected in traditional oil paintings in layers containing the pigment lead-tin yellow type I (LTY-I). LTY-I has been used by artists from at least the second quarter of the 15th century until the first half of the 18th century. Soap formation can lead to protrusions in paint layers and increased transparency, causing the paint support to become visible. We have characterized LTY-I by (119)Sn and (207)Pb solid-state NMR (ssNMR) spectroscopy. Using a combination of NMR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 51 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…3A, curve a) with clear chemical shifts at -608, -670 and -728 ppm. The first one (at -608 ppm) is assigned to SnOx clusters and is in agreement with previous reports for SnO2 species, 21 with the magnitude of this peak being dependent on the degree of SnOx oligomerization. However, the other two chemical shifts (at -670 and -728 ppm) are ascribed to hydrated, Sn(IV) species in Td sites (closed and/or open sites).…”
Section: Sn Mas Nmrsupporting
confidence: 92%
See 1 more Smart Citation
“…3A, curve a) with clear chemical shifts at -608, -670 and -728 ppm. The first one (at -608 ppm) is assigned to SnOx clusters and is in agreement with previous reports for SnO2 species, 21 with the magnitude of this peak being dependent on the degree of SnOx oligomerization. However, the other two chemical shifts (at -670 and -728 ppm) are ascribed to hydrated, Sn(IV) species in Td sites (closed and/or open sites).…”
Section: Sn Mas Nmrsupporting
confidence: 92%
“…119 Sn MAS-NMR has been used extensively for probing the nature of Sn species in zeolites, [21][22][23] and these interpretations can be rationally extended for probing analogous species in AlPO-5. In Fig.…”
Section: Sn Mas Nmrmentioning
confidence: 99%
“…reproduction of historical recipes is fundamental to assess these different aspects, and determine if the painter prepared the soaps him/herself on purpose or if they appeared naturally. Different works report the study of reactions of lead compounds with organic binders (usually oil, sometimes egg yolk, beeswax, or resin), ranging from the preparation of simple binary mixtures, up to the accurate reproduction of historical recipes (Meilunas et al, 1990;Mecklenburg & S., 2001;Erhardt et al, 2005;Carlyle, 2006;Cotte et al, 2006Cotte et al, , 2007Boon et al, 2007;Carlyle et al, 2008;Mazzeo et al, 2008;Salvadó et al, 2009;Bonaduce et al, 2012aBonaduce et al, , 2012bDuce et al, 2013;Pratali, 2013;Catalano et al, 2014a;Osmond, 2014;Pallipurath et al, 2015;de Viguerie et al, 2016). An interesting observation is given by Mazzeo et al who reported the FTIR analysis of model paintings prepared by mixing oil and egg yolk with 42 different pigments, among which included eight lead-based compounds, after 10 years of natural aging (Mazzeo et al, 2008).…”
Section: Confrontation Of Historical Texts With Experimental Observatmentioning
confidence: 99%
“…[18] When these soaps aggregate,m igrate,a nd crystallize,s ignificant damage can occur to paint layers. [18] When these soaps aggregate,m igrate,a nd crystallize,s ignificant damage can occur to paint layers.…”
Section: Angewandte Chemiementioning
confidence: 99%